Pengaruh Instagram Terhadap Sikap Toleransi pada Siswa SMA Al Islam 1 Surakarta - Muhammad Abduh Alfaruqie; Silvia Estefina Subitmele; Cut Rayhanun Hafizah R; Naela Faza Fariha (Indra institute Research & Publication, 2023)
A person's tolerance is influenced by many factors, be it the environment, family, habits etc. In the era of technological development 4.0, media and information technology has developed quite rapidly, which is thought to influence a person's social attitudes. The purpose of this study was to find out whether Instagram social media affects the tolerance attitude of SMA Al Islam 1 Surakarta students. The method used in this study is a quantitative method, by examining the relationship between two variables using a statistical test assisted by the SPSS application. The results showed that there was an influence between the use of social media Instagram on the tolerance attitude of SMA Al Islam 1 Surakarta students. Instagram had a 15.4% influence in determining student tolerance, while 84.6% was influenced by other variables not included in the research object.